APPLICATION OF STEM CELLS AND PRECURSOR CELLS FOR STIMULATION OF ORGAN REVASCULARIZATION AND REGENERATION - M. V. Eremeeva (Вестник трансплантологии и искусственных органов)
Different angiogenic factors induced angiogenesis stimulation in ischemic tissues stays in the focus of scientific research for long time. The key role in ischemic angiogenesis belongs to endothelial precursor cells, plenty of which are reserved in bone marrow. Resident endothelial precursor cells are also found in some tissues and in circulation. These cells are involved in neoangiogenesis as well. Theoretically, injection of exogeneous endothelial precusor cells might contribute to restoration of circulation in the ischemic organ. Various types of cells have been approved for regeneration stimulation in a number of experimental protocols. A various degree of improvement of myocardial contractive function has been obtained as a universal result of these investigations, though the mechanisms underlying observed effect remain evasive. The paper focuses on advantages and drawbacks of embryonic, hematopoetic and mesenhimal stem cells application for angiogenesis stimulation and organs and tissues regeneration.